Listy Chopina i do Chopina jako źródło informacji do badań nad rodziną Tytusa Woyciechowskiego - Mardofel, Bogdan (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
Fryderyk Chopin corresponded with many people and his letters are a very rich source of information about people and events of that time. The letters exchanged between Chopin and other people comprise a very important source of information used for biografy of many persons, especially Chopin's greatest friend – Tytus Woyciechowski. They also show the influence of Woyciechowski on his work and present the relationship between Tytus Woyciechowski and Fryderyk Chopin during the 31 years of their acquaintance. The sketches of the family members biografy are also presented in the research: the mother of Titus Woyciechowski, Marianna, half-siblings Antonina and Karol Weltz, cousin Marianna Bogusz and his brothers-in-law Rajmund Rembieliński, Leopold Poletyło and Wincenty Skarzyński.